2013
DOI: 10.4314/ajid.v7i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing influenza positivity rates by Real-Time RT-PCR, Elisa and viral culture methods in Côte d’Ivoire, West Africa, in 2009

Abstract: Detection of circulating influenza strains is a key public health concern especially in limited-resource settings where diagnosis capabilities remain a challenge. As part of multi-site surveillance in Côte d'Ivoire during the 2009 influenza A(H1N1) pandemic, we had the opportunity to test respiratory specimens collected from patients with acute respiratory illness (ARI). We analyzed and compared the percentage of specimens testing positive using three laboratory methods (rtRT-PCR, ELISA, viral culture). From J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study conducted by Lednicky et al (2013), attempted to detect and isolate airborne influenza from a reported respiratory illness outbreak by using an ELISA (Lednicky, Loeb et al 2013). Nzussouo et al (2013) found that using an ELISA test for the detection of influenza was slower and less sensitive when compared to using qPCR as the detection method (Nzussouo, Kadjo et al 2013).…”
Section: Quantification Of Influenza Virusmentioning
confidence: 99%
“…A study conducted by Lednicky et al (2013), attempted to detect and isolate airborne influenza from a reported respiratory illness outbreak by using an ELISA (Lednicky, Loeb et al 2013). Nzussouo et al (2013) found that using an ELISA test for the detection of influenza was slower and less sensitive when compared to using qPCR as the detection method (Nzussouo, Kadjo et al 2013).…”
Section: Quantification Of Influenza Virusmentioning
confidence: 99%